Modeling the Electrostatic Deflection of a MEMS Multilayers Based Actuator. (8th December 2013) - Ouakad, Hassen M.; Hawwa, Muhammad A.; Al-Qahtani, Hussain M.
Abstract : An actuator comprised of a rigid substrate and two parallel clamped-clamped microbeams is modeled under the influence of electrostatic loading. The problem is considered under the context of nonlinear Euler's mechanics, where the actuating system is described by coupled integrodifferential equations with relevant boundary conditions. Galerkin-based discretization is utilized to obtain a reduced-order model, which is solved numerically. Actuators with different gap sizes between electrode and beams are investigated. The obtained results are compared to simulations gotten by the finite-element commercial software ANSYS.